The Impact of Mindfulness-Based Interventions on Stress and Anxiety Among Nurses - Sultan Juhaz mohsen Almutairi,; Essa hamad almutiri,; Abdullah Hamoud Alsubaie,; Nouf Sand Al-Qahtani,; Jamelah Ali Alyami,; Raghad Zafer Alshehri,; Maha Mesfer Alsubaie,; Mohammed Faris alanazi,; Yousef Abdulaziz Al-Khalidi,; Gharam Ahmed Ibrahim Aljayzani,; Abdullah Mohammed Radhi AlSurayhi1, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Nurses face significant psychological challenges due to the demanding nature of their profession, including high levels of stress, anxiety, and burnout. These challenges not only impact nurses' well-being but also compromise the quality of patient care. Mindfulness-based interventions (MBIs) have emerged as effective therapeutic approaches to mitigate these issues by fostering present-moment awareness, emotional regulation, and resilience. This paper explores the psychological burden of nursing and examines the evidence supporting MBIs, including Mindfulness-Based Stress Reduction (MBSR), Mindfulness-Based Cognitive Therapy (MBCT), and other innovative approaches such as Mindfulness-Based Art Therapy (MBAT). Empirical studies and systematic reviews demonstrate that MBIs significantly reduce stress and anxiety, improve emotional regulation, enhance sleep quality, and lower rates of burnout among nurses. Mechanisms underlying these benefits include neurobiological adaptations, reductions in rumination, improved coping strategies, and the activation of the parasympathetic nervous system. Furthermore, the flexibility of online and brief mindfulness programs increases accessibility for nurses with demanding schedules. By integrating MBIs into nursing education and workplace wellness programs, healthcare organizations can support nurses' mental health, promote job satisfaction, and enhance patient care. This paper highlights the critical role of MBIs in fostering a healthier and more resilient nursing workforce.